A laboratory guide to the mammalian embryo - Gardner, David K.; Lane, Michelle; Watson, Andrew J. (Andrew John), 1959- (Oxford University Press, 2004)
This book pulls together the full range of cell culture, biochemical, microscopic, and genetic techniques to study the early mammalian embryo. Until now, there has never been such a comprehensive compendium, though there have been more focused books of protocol, such as "Manipulating the Mouse Embryo", from Cold Spring Harbor. This book is intended to appeal to all constituencies, from basic experimental science to clinical and animal science applications.